Tax Training for Members of Hisfarma Special Region of Yogyakarta - Utomo, Rochmad Bayu; Nugraeni; Pertiwi, Ni Luh Gde Ana; Karista, Dina; Dini Hari, Ilham Galih (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: The rapid growth of pharmacies has made them a key focus for government taxation. However, many pharmacy entrepreneurs struggle with tax compliance due to a lack of knowledge. This study aims to address this issue through taxation training to enhance their understanding and adherence to tax regulations. Method: The study involved 35 HISFARMA pharmacy entrepreneurs in Yogyakarta, using observation, training, and mentoring to improve tax knowledge and compliance. Practical Application: The training provided entrepreneurs with essential taxation knowledge, enabling better compliance and reducing business risks related to tax obligations. Conclusion: The training significantly improved participants' understanding of pharmacy taxation, fostering better compliance and supporting a more structured business environment.